Unlawful Acts as an Instrument of Accountability in Natural Resources Management - Pahlefi, Pahlefi; Muskibah, Muskibah; Suryahartati, Dwi (Fakultas Hukum Universitas Jambi, 2026)
Natural resource management in Indonesia is still faced with environmental damage, conflicts of interest, and weak legal accountability, where administrative compliance is often used as legitimacy even though the activities carried out have significant ecological and social impacts. This article formulates the problem of how the concept of Unlawful acts can be reconstructed to function as an instrument of accountability in natural resource management, as well as bridging civil law and state administrative law in enforcing legal responsibility for environmental damage. This study concludes that Unlawful acts can no longer be interpreted narrowly as a violation of written norms that cause individual harm, but must be understood substantively as a violation of the principles of environmental protection, ecological justice, and people's rights to a good and healthy environment. Administrative permits cannot be used as absolute legitimacy if business activities are proven to cause damage to natural resources. Unlawful acts functions as an instrument of accountability that is substantive, preventive, corrective, and as a control of power. Therefore, it is recommended to strengthen the progressive interpretation of Unlawful acts by the courts and harmonize regulations across legal regimes so that Unlawful acts can effectively realize fair, responsible, and sustainable natural resource governance.